Empowerment of Homestay Owners for Business Standards Fulfilment - Levyda Levyda; Ekayana Sangkasari Paranita; Giyatmi Giyatmi (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
Increasing the number of tourists to Harapan Island in the Kepulauan Seribu triggers an increase in the number of homestays. But there are still many homestays that do not meet operational standards. The purpose of empowerment is to increase the capability of homestay owners in meeting business standards. The analytical method used is a method of self reflection. The participants are guided by the facilitators for self-reflection on the homestay and its management. Most homestays have two rooms. Most homestays are separate from where the owner lives, only a few offer homestays with the owner. Most homestays do not have signage, do not provide kitchen facilities for guests, and have no complaint records. The majority of homestay owners have not yet attended homestay and ‘sapta pesona’ training. The interaction between homestay owners and guests is relatively low because most guests book rooms through travel agents. Therefore, most homestay owners do not record guest identity. Most homestay owners also do not have a special room for administrative activities, and do not do regular guest and financial administration activities. The capabilities of homestay owners in meeting business standards vary so that empowerment activities are strongly recommended.